Sleep duration mediates the association between heavy metals and the prevalence of depression: an integrated approach from the NHANES (2005–2020) - Mao, Qingsong; Zhu, Xiaoyi; Kong, Yuzhe (Frontiers in Psychiatry, 2024)
Abstract Purpose This study investigates the association between heavy metal exposure and the prevalence of depression, with the mediating role of sleep duration. Method Our study investigated the association between heavy metal concentration and depression risk in the NHANES from 2005 to 2020. We used logistic regression analysis, WQS regression model and BKMR model to assess the association. Mediation analysis was performed to explore the role of sleep duration in heavy metal exposure-induced depression. Result Of the 10825 individuals included in this study, 705 (6.85 %) were diagnosed with depression. We found a positive association between the cadmium (Cd), cobalt (Co), lead (Pb), antimony (Sb), wolfram (W) concentration and the prevalence of depression. Moreover, heavy metals mixtures were positively correlated with the prevalence of depression, with Cd identified as the main contributor in the WQS regression model (0.4654). Furthermore, sleep duration mediated the association between Cd, molybdenum (Mo), Pb, Sb, W exposure and prevalence of depression, explaining 3.12%, 15.84%, 18.24%, 9.56%, 3.68% of the effect. Conclusion The findings affirm that heavy metal exposure is linked to higher depression incidence and that this relationship is partly mediated by sleep duration alterations. The study underscores the importance of environmental health monitoring and interventions aimed at reducing heavy metal exposure to mitigate its psychological impacts.